Original paperRole of insulin-like growth factor 1 in stent thrombosis under effective dual antiplatelet therapy - Yalcin, Ahmet Arif; Topuz, Mustafa; Biyik, Ismail; Akturk, Ibrahim Faruk; Celik, Omer; Isiksacan, Nilgun; Yalcın, Burce; Birant, Ali; Uzun, Fatih (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
Introduction: Accumulating evidence now indicates that insulin-like growth factors (IGF) and their regulatory proteins are growth promoters for arterial cells and mediators of cardiovascular diseases. Aim : We hypothetised that IGF-1 levels could play a role in the development of stent thrombosis (ST), and aimed to investigate the associations between stent thrombosis under effective dual antiplatelet therapy and IGF-1 levels and other related factors such as disease severity and LV ejection fraction in patients undergoing coronary stent placement. Material and methods : A total of 128 patients undergoing coronary stent implantation were included in the analysis. Seventy-seven patients experiencing ST in the first year after stent implantation were defined as the ST group. Fifty-one patients without ST at least 1 year after stent implantation were defined as the no-thrombosis (NT) group. The IGF-1 levels, Gensini scores, and other related factors were measured. Results : The IGF-1 levels were significantly higher in the stent thrombosis group than in the no-thrombosis group (122.22 ±50.61 ng/ml vs. 99.52 ±46.81 ng/ml, respectively, p < 0.039). The left ventricle ejection fraction (LVEF) values were significantly lower (44.13 ±9.25% vs. 55.81 ±8.77%, p < 0.0001) and Gensini scores were significantly higher (63.74 ±26.54 vs. 48.87 ±23.7, p < 0.004) in the ST group than in the NT group, respectively. In the linear regression analysis, IGF-1, Gensini score, LVEF, total cholesterol, and triglycerides were found to be independent risk factors for ST. Conclusions : This study revealed that the plasma IGF-1 levels, disease severity, were significantly higher and LVEF was lower in patients with ST. High IGF-1 levels may identify patients who are at increased risk for ST. Future trials are necessary to confirm these results.